2003
DOI: 10.1046/j.1351-5101.2003.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of cytokine (tumor necrosis factor‐alpha, interleukin‐6, interleukin‐10) concentrations in the cerebrospinal fluid of female patients with multiple sclerosis and systemic lupus erythematosus

Abstract: Humoral immune response seems to play a role in the pathogenesis of multiple sclerosis (MS) and in the central nervous system (CNS) complications of systemic lupus erythematosus (SLE). The aim of the present study was to compare the levels of tumor necrosis factor-alpha (TNF-alpha), interleukin-6 (IL-6) and IL-10 in the cerebrospinal fluid of female patients with several forms of MS (50 patients), and in female patients with several types of CNS complications in SLE (50 patients). Samples were investigated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 25 publications
1
26
0
2
Order By: Relevance
“…The previous studies showed that Th1 cytokines appear to play a role in autoantibody production [14,15]. The proinflammatory IL-6 may also play a role in autoimmune diseases; however, this pleiotropic cytokine is thought to be of pivotal importance for immune regulation through its action on both B and T cells [16].…”
Section: Introductionmentioning
confidence: 98%
“…The previous studies showed that Th1 cytokines appear to play a role in autoantibody production [14,15]. The proinflammatory IL-6 may also play a role in autoimmune diseases; however, this pleiotropic cytokine is thought to be of pivotal importance for immune regulation through its action on both B and T cells [16].…”
Section: Introductionmentioning
confidence: 98%
“…In addition, there is a genetic association between TNF-polymorphism and susceptibility to SLE [86]. Also, TNF-may account for abnormal responses within the CNS during the development of NPSLE, based on the evidence for elevated expression of TNF-in the CNS in parallel with neuropsychiatric syndrome [39,57].…”
Section: Tnf-mentioning
confidence: 98%
“…The involvement of IL-10 in NPSLE has been investigated by several researchers. Increased levels of IL-10 in CSF were detected in a patient with NPSLE [38,39]. Of interest, Rood et al have shown that the IL-10 promoter haplotype ATA was found to be associated with the phenotype of SLE with neuropsychiatric manifestations, whereas the GCC haplotype was less frequent in these patients [40].…”
Section: Il-10mentioning
confidence: 98%
See 1 more Smart Citation
“…It is characterized by areas of inflammation are control groups with inflammatory and neurological diseases other 128 than MS. Although they are often discriminated in 'non-inflammatory' 129 and 'inflammatory' disease controls, control cohorts are oftentimes in- 130 homogeneous and not well characterized in literature [15]. Therefore, 131 the BioMS-eu network proposed "consensus definitions and application 132 guidelines for control groups" of CSF biomarker studies in MS [15].…”
mentioning
confidence: 99%